The Potential of Different Experimental Designs for Policy Impact Assessment - Sven Grun̈er; Norbert Hirschauer; Oliver Mußhoff (German Journal of Agricultural Economics (GJAE), 2016)
Economic experiments have traditionally been conducted in laboratory settings. Since experimental conditions can be easily controlled and manipulated in the lab, high internal validity can be achieved. The external validity of lab experiments, however, is often poor due to the highly stylized environment. Hence, in recent years, researchers have increasingly left the lab and used the Internet to
Keywords: 330